IEEE INFOCOM 2018 - IEEE Conference on Computer Communications Workshops (INFOCOM WKSHPS) 2018
DOI: 10.1109/infcomw.2018.8406981
|View full text |Cite
|
Sign up to set email alerts
|

Rumba: A python framework for automating large-scale Recursive Internet Experiments on GENI and FIRE+

Abstract: A number of recent EU-funded projects have been investigating the Recursive Internet Architecture (RINA). IRATI built an initial prototype implementation, which was extended by the PRISTINE project towards technology demonstrators showing the feasibility of the architecture and demonstrating how RINA tackles security and reliability and how it can simplify network management. Currently, ARCFIRE sets out to evaluate realistic network scenarios, scaling up experiments in terms of numbers of nodes, services and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Both observations are of course simply because more hops are used to reach the destination. We demonstrated that the experiment is very reproducible, largely thanks to Rumba [10].…”
Section: Resiliency Experimentsmentioning
confidence: 87%
See 1 more Smart Citation
“…Both observations are of course simply because more hops are used to reach the destination. We demonstrated that the experiment is very reproducible, largely thanks to Rumba [10].…”
Section: Resiliency Experimentsmentioning
confidence: 87%
“…These tools showed it was necessary to automate the execution of large experiments, since doing this manually is error-prone, hard to reproduce, and very time consuming. To fill this gap, ARCFIRE developed Rumba [10]. Rumba is an experimentation framework that supports existing testbeds provided by the American GENI (Global Environment for Network Innovation) and the European FIRE initiatives via the jFed and Emulab experiment management software.…”
Section: Scaling Up Rina Networkmentioning
confidence: 99%
“…Ouroboros 2 is a novel (recursive) network architecture that incorporates the experience we gained during research collaborations on RINA [108], as well as a thorough revisiting of a lot of early network research literature that formed the origins for most computer networking concepts. From a high level perspective, Ouroboros looks very similar to RINA, as evidenced by the Rumba [107] framework, which can be used to deploy the IRATI [38] and rlite [66] RINA implementations as well as our Ouroboros prototype [100]. The system research approach [83] to building Ouroboros adopts the UNIX design philosophy where each program does one thing well [69].…”
Section: Introductionmentioning
confidence: 99%